The unfavorable effect of ceo narcissism: The role of the audit committee: - Wijaya, Riesanti Edie; Mansula Kweniati, Coansheline Amathya (Universitas Hayam Wuruk Perbanas, 2024)
Narcissism is often considered a behavioral disorder that has negative im-pacts, especially for top management. The audit committee, as part of the governance system, plays a major role in suppressing such negative behav-ior. The purpose of this study is to examine the role of the audit committee in suppressing the negative impacts of CEO narcissism. This quantitative research uses secondary data obtained from the websites of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2017 – 2020, consisting of 266 companies. Sampling is conducted using purpos-ive sampling method. The operational variables used in this study are CEO narcissism, audit committee, and tax avoidance. The results of this study show that CEO narcissism has a negative and significant effect on effective tax rate (ETR). In addition, the results of this study also show that the audit committee (AC) is unable to influence management decisions in car-rying out tax avoidance. The agency theory is unable to explain how the audit committee positions itself in narrowing asymmetry of information between agents and principals. On the other hand, institutional theory can explain the inability of the audit committee in carrying out its monitoring function. According to institutional theory, the existence of an audit committee in the company is merely a formality.